Prenatal Antidepressant Exposure and Risk of Spontaneous Abortion – A Population-Based Study - Kjaersgaard, Maiken Ina Siegismund (Public Library of Science, 2013)
PURPOSE: To estimate the risk of spontaneous abortion after use of antidepressant medication during pregnancy. METHODS: From the Danish Medical Birth Registry and the Danish National Hospital Registry, we identified all pregnancies leading to in- or outpatient contacts in Denmark from February 1997 to December 2008. The Danish Registry of Medicinal Product Statistics provided information on the women's prescriptions for antidepressants during pregnancy. We obtained information on women who were diagnosed with depression from the Danish Psychiatric Central Registry. Adjusted relative risks (aRR) of spontaneous abortion were estimated according to exposure to antidepressants or maternal depression using binomial regression. RESULTS: Of the 1,005,319 pregnancies (547,300 women) identified, 114,721 (11.4%) ended in a spontaneous abortion. We identified 22,061 pregnancies exposed to antidepressants and 1,843 with a diagnosis of depression with no antidepressant use, of which 2,637 (12.0%) and 205 (11.1%) ended in a spontaneous abortion, respectively. Antidepressant exposure was associated with an aRR of 1.14 (95% confidence interval (CI) 1.10–1.18) for spontaneous abortion compared with no exposure to antidepressants. Among women with a diagnosis of depression, the aRR for spontaneous abortion after any antidepressant exposure was 1.00 (95% CI 0.80–1.24). No individual selective serotonin reuptake inhibitor (SSRI) was associated with spontaneous abortions. In unadjusted analyses, we found that mirtazapine, venlafaxine, and duloxetine were associated with spontaneous abortions among women with depression but we had no information on potential differences in disease severity and only few pregnancies were exposed in the population. CONCLUSION: We identified a slightly increased risk of spontaneous abortion associated with the use of antidepressants during pregnancy. However, among women with a diagnosis of depression, antidepressants in general or individual SSRI in particular were not associated with spontaneous abortions. Further studies are warranted on the newer non-SSRI antidepressants, as we had insufficient data to adjust for important confounding factors.